2018
DOI: 10.1111/een.12687
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic niche differentiation in West African savannah termites as indicated by stable isotopes

Abstract: 1. Termites consume a wide range of plant material at different stages of decomposition and, accordingly, have been classified into ‘feeding groups’. African savannah ecosystems harbour many termite species, yet most belong to Termitidae. Especially striking is the co‐occurrence of up to eight Macrotermitinae and five Trinervitermes species, each having apparently identical trophic niches, i.e. fungus‐growers and grass‐feeders, respectively.2. This study examined stable isotope signatures of 15N and 13C of Wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 40 publications
3
7
1
Order By: Relevance
“…Noteworthy, our study is limited to temperate forests with C3 vegetation type. The difference in δ 13 C values between plants with C3 and C4 photosynthesis observed, for example, in savannas provides more variable isotopic background and thus may serve as a promising framework to study niche conservatism in feeding strategies and resource specialization of animals (Codron et al, ; Schyra, Scheu, & Korb, ).…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, our study is limited to temperate forests with C3 vegetation type. The difference in δ 13 C values between plants with C3 and C4 photosynthesis observed, for example, in savannas provides more variable isotopic background and thus may serve as a promising framework to study niche conservatism in feeding strategies and resource specialization of animals (Codron et al, ; Schyra, Scheu, & Korb, ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the authors reported significant differences in the δ 13 C and δ 15 N values between castes of the same colony suggesting that the nutritional contribution of fungal symbiont (Termitomyces) varies between castes within the same colony [40]. These studies demonstrate the utility of adding to the African termite isotope database while distinguishing between taxa, habitat type, seasonality, as well as caste (see also [60][61][62]).…”
Section: Introductionmentioning
confidence: 84%
“…Further, one should note that previous studies [58,60] that found substantially higher δ 13 C values in Macrotermes, were conducted in environments outside of the range of extant chimpanzees, which suggest that these locations lack the climate and vegetation structure chimpanzees need to survive. Direct comparisons between the Macrotermes isotope values presented here and in previous studies are further complicated due to varying sampling methodologies.…”
Section: Plos Onementioning
confidence: 91%
“…The only studies directly comparable to our study come from Africa. There phylogenetic community analyses imply random processes [49], but also evidence for interspecific competition [12,71] and environmental filtering [13], depending on the study site, disturbance regime, and presence of a dominant mound building termite species. Thus, we currently cannot derive any general conclusions and more similar studies are needed.…”
Section: Discussionmentioning
confidence: 99%